JSPS-3 Detection of Pathogens Associated with Bovine Respiratory Disease: Clinical Cases in Thai Dairy Herds - Kittisak Ajariyakhajorn; Thanasak Boonserm; Sukuma Samngamnim (Hemera Zoa, 2018)
Bovine respiratory disease (BRD) is the major source of economic loss for the cattle industry. The major respiratory pathogens, such as bovine respiratory syncytial virus (BRSV), bovine viral diarrhea virus (BVDV), bovine herpesvirus type1 (IBR), Parainfluenza 3 (PI3) virus impaired the animal’s respiratory defenses in which Pasteurella multocida, Histophilus somni, Mannheimia haemolytica and Mycoplasma bovis caused the complex of respiratory disturbances. The investigation of clinical cases of BRD in dairy farms supports the information for control and treatment strategies. We aim to investigate pathogens that associated with clinical cases of bovine respiratory disease in Thai dairy herds.